Representation of guardian spirits through dayak motifs: a visual language analysis of rumah betang murals in West Kalimantan - Della Maharani, Utin; Prilosadoso, Basnendar Herry (Gelar: Jurnal Seni Budaya, 2025)
This research explores the symbolic visual language of guardian spirit motifs depicted in the mural of Rumah Betang, located in Jalan Sutoyo, Pontianak, West Kalimantan. The mural features visual representations of ancestral guardian spirits, the hornbill (enggang), and the serpent (Nabau), which are central to Dayak cosmology and spiritual beliefs. Using a qualitative descriptive approach and visual language theory by Primadi Tabrani, the study analyzes the content (wimba), visual strategy (way of wimba), and expression structure of the mural. Field observation and interviews with Dayak cultural actors support the interpretation of visual elements and their symbolic functions. The guardian spirit is positioned at the top to signify spiritual authority; the hornbill at the center represents a divine messenger; and the Nabau at the base reflects foundational protection. Tendrils and spirals serve to connect these figures, symbolizing the cycle of life and balance between natural and spiritual realms. This research contributes to a deeper understanding of how visual art encodes cultural narratives, spiritual structures, and protective symbolism within the Dayak community.